Evolution of solidification structure, primary phase and wear properties of Sn–11wt%Sb alloy ingots under permanent magnet stirring. Issue 21 (2nd November 2021) - Wang, Wanlin; Peng, Jianfei; Zeng, Jie; Zhu, Chenyang; Yang, Yindong; McLean, Alex
ABSTRACT: An experimental investigation has been conducted with respect to the influence of permanent magnet stirring (PMS) under different rotation speeds (0, 60, 120, 180 rpm) on the evolution of solidification structure, primary Sn4 Sb3 phase and wear properties of Sn–11wt%Sb alloy. The results revealed a significant increase in the flow intensity of the liquid, improvement in the grain and eutectic microstructure refinement, and decrease of solidification cavities with increasing rotation speed. Besides, when the rotation speed increased from 0 to 180 rpm, the difference in the area proportion of the Sn4 Sb3 phase between upper and lower parts of the alloy ingots decreased from 17.05% to 0.41%, resulting in a more uniformly distributed primary phase along the longitudinal direction. In addition, with enhanced stirring intensity, a primary phase-rich layer was formed at the surface of the ingot close to the mould wall, and the average equivalent diameters of the primary phase were increased. Moreover, tribological test results suggested that magnetic stirring could improve the wear resistance of the alloy by decreasing the friction coefficient from 0.77 to 0.72 and reducing the width of the worn surface from 1.51 to 0.81 mm due to the PMS-driven uniform distribution of the reinforcing primary phase.